A case of autoimmune GFAP astrocytopathy with profound weight loss and increased uptake in the spinal cord on 18F‐FDG PET. Issue 1 (22nd October 2020) - Osakada, Yosuke; Omote, Yoshio; Ikegami, Ken; Tadokoro, Koh; Sato, Kota; Hishikawa, Nozomi; Takemoto, Mami; Ohta, Yasuyuki; Yamashita, Toru; Kimura, Akio; Abe, Koji
Abstract: A 76‐year‐old man presented with subacute onset of progressive cognitive impairment, anorexia, tremor, ataxic gait, and urinary dysfunction. He had lost 17 kg in 9 months before his admission (due to persistent anorexia). A brain MRI showed a typical radial pattern of periventricular gadolinium enhancement and longitudinally extensive hyperintensity from cervical to lumbar spinal cord. 18 F‐ FDG PET newly revealed an increased uptake of the tracer in the cervical and lower thoracic cords. After an intravenous methylprednisolone (1000 mg/d for 3 days) followed by oral prednisolone 40 mg/d, his clinical symptoms and abnormal MRI lesions improved. Anti‐GFAP antibodies were subsequently identified in CSF obtained on admission, confirming the diagnosis of autoimmune GFAP astrocytopathy.